2013
DOI: 10.5194/acpd-13-7737-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model calculated global, regional and megacity premature mortality due to air pollution

Abstract: Air pollution by fine particulate matter (PM2.5) and ozone (O3) has increased strongly with industrialization and urbanization. We estimated the premature mortality rates and the years of human life lost (YLL) caused by anthropogenic PM2.5 and O3 in 2005 for epidemiological regions defined by the World Health Organization. We carried out high-resolution global model calculations to resolve urban and industrial regions in greater detail compared to previous wor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
19
2
Order By: Relevance
“…The Global Burden of Disease estimates ranks pollution as the fifth largest killer in India [ World Health Organization ( WHO ), ]. Estimates of the respiratory mortality show India to rank second among the countries globally affected by PM 2.5 [ Silva et al ., ] and O 3 pollution [ Lelieveld et al ., ]. It is anticipated that recent upward trends in transportation, industrial and energy sectors, urbanizations, population growth in India along with climate change will raise the levels of O 3 and PM 2.5 in the future, which could worsen the vulnerability of a growing population.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Burden of Disease estimates ranks pollution as the fifth largest killer in India [ World Health Organization ( WHO ), ]. Estimates of the respiratory mortality show India to rank second among the countries globally affected by PM 2.5 [ Silva et al ., ] and O 3 pollution [ Lelieveld et al ., ]. It is anticipated that recent upward trends in transportation, industrial and energy sectors, urbanizations, population growth in India along with climate change will raise the levels of O 3 and PM 2.5 in the future, which could worsen the vulnerability of a growing population.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has reported that ambient air pollution was responsible for 3,700,000 deaths in 2012, including 16% of the lung cancer deaths, 11% of the chronic obstructive pulmonary diseaserelated deaths, 29% of the heart disease and stroke deaths, and approximately 13% of the deaths that were due to respiratory infections (Lee et al, 2014). Lelieveld et al (2013) calculated a global mortality of approximately 773,000/year due to respiratory disease, 186,000/year due to lung cancer and 2,000,000/year due to cardiovascular disease (CVD) resulting from exposure to anthropogenic PM 2.5 (Lelieveld et al, 2013). Obviously, CVD is a key contributor to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…India is the world's second most populous country and is undergoing rapid industrialization, urbanization and economic development (United Nations, ). It is also an air pollution mortality hot spot, with >500,000 premature deaths each year (GBDMWG, ; Ghude et al, ; Lelieveld et al, , ). However, India is highly understudied in terms of atmospheric composition: In‐situ measurements are too sparse to reliably assess the importance of different emission sources for air quality.…”
Section: Introductionmentioning
confidence: 99%